PENGARUH TACIT KNOWLEDGE TERHADAP INOVASI PRODUK PADA INDUSTRI KREATIF KERAJINAN DI KABUPATEN MINAHASA, SULAWESI UTARA - Leonardus Ricky Rengkung; Lyndon R. J. Pangemanan; Lorraine W.Th. Sondak (MIX: JURNAL ILMIAH MANAJEMEN, 2019)
The purpose of this study is to analyze the ability and analyze the effect of tacit knowledge to product innovation on Creative Craft Industry at Minahasa, North Sulawesi. To answer these purposes, the 60 firms of creative craft are being taken by purposive sampling and Logistic Regression is being applied to those 60 firms of creative craft. Results show that there are 16 firms that are able to produce innovative product and 44 firms that are not able to produce innovative product. Of the 16 innovative firms, it is predicted that there are 6 firms obviously will be able to produce innovative product, and 10 firms are unable to produce innovative product. Of the 44 not innovative firms, it is predicted that there are 42 firms obviously will be unable to produce innovative product but there are 2 firms are able to produce innovative product. Three factors of tacit knowledge, i.e. action learning, concious awareness and demonstrability have a significant effect on innovative product, whereas the four factors of express ability, formal education, informal education and personal experience have no significant effect. It can be concluded that tacit knowledge have an important role to produce innovative products especially in exploiting and exploring three factors of tacit knowledge, i.e. action learning, concious awareness and demonstrability.